(d)Eficiencia en el uso del smartphone y las redes sociales en la acción pastoral de los agentes de la Iglesia de Aragón - Fandos Igado, Manuel; Ordoñez-Fernández, Feliciano-Francisco; Pérez-Escoda, Ana (Revistas - Revista Mediterránea de Comunicación, 2018)
El presente trabajo responde a la necesidad de determinar el uso que hacen de las redes sociales (RRSS) los agentes pastorales de la Iglesia católica aragonesa en sus tareas pastorales y evangelizadoras. Es un estudio cuantitativo sobre una muestra representativa en que queda evidenciado que, a pesar de las posibilidades que estos nuevos medios ofrecen en la tarea educativa y comunicativa, los agentes pastorales los utilizan deficientemente en su tarea ministerial y están presentes mayoritariamente en redes cada vez menos frecuentadas por los jóvenes adolescentes. Un estudio que abre las puertas a futuras investigaciones relativas a determinar la importancia de esta variable en la desafección de la juventud aragonesa con el mensaje y el compromiso cristiano que se intuye y, llegado el caso, profundizar en modelos de comunicación, estrategias de acompañamiento, estructuras lingüísticas, tipos de lenguaje y hasta vocabulario que merecería revisarse para hacer presente y significativo el mensaje cristiano en los nuevos espacios de socialización juvenil. | This work seeks to determine the use made of social networks by pastoral agents of the Aragonese Catholic Church in performing their pastoral and evangelising tasks. It is a quantitative study on a representative sample, revealing that the pastoral agents are ineffective in use of the social networks in their ministerial office and that they are mainly active on those social networks less frequented by young adolescents, despite all the possibilities afforded in education and communication by these new media. This study will be of use in future research on determining the importance of this variable in the disaffection of Aragonese youth with the message and Christian commitment expounded and, where necessary, delving into communication models, support strategies, linguistic structures, types of language, including vocabulary that should be revised to make the Christian message present and meaningful in the new areas of youthful socialisation.
(d)Efficiency in use of the Smartphone and social networks by agents of the Church of Aragon in the course of their pastoral work
This work seeks to determine the use made of social networks by pastoral agents of the Aragonese Catholic Church in performing their pastoral and evangelising tasks. It is a quantitative study on a representative sample, revealing that the pastoral agents are ineffective in use of the social networks in their ministerial office and that they are mainly active on those social networks less frequented by young adolescents, despite all the possibilities afforded in education and communication by these new media. This study will be of use in future research on determining the importance of this variable in the disaffection of Aragonese youth with the message and Christian commitment expounded and, where necessary, delving into communication models, support strategies, linguistic structures, types of language, including vocabulary that should be revised to make the Christian message present and meaningful in the new areas of youthful socialisation.
Keywords: smartphone; redes sociales; evangelización; acción pastoral; agentes pastorales; iglesia católica; social networks; evangelism; pastoral work; pastoral agents; catholic church; Emerging